Frequency of factor V Leiden (G1691A) and prothrombin (G20210A) polymorphisms in Population of Kerman Province, Iran - Nasrollah Saleh-gohari; Neda Salmani-Cheharfarsakhi (Journal of Kerman University of Medical Sciences, 2017)
Background & Aims:Thromboembolism is an acute cardiovascular disease that ranges from clinically unimportant to massive embolism. Both acquired and hereditary risk factors contribute to the disease. We aimed to determine the prevalence of two hereditary predisposing factor of the disease, prothrombin G20210A and factor V Leiden (G1691A) polymorphisms, in Kerman population. Methods:factor V and factor II genes of 112 healthy individuals were examined to detect factor V Leiden (G1691A) and prothrombin G20210A variants. Genomic DNA of subjects was isolated from leukocytes of the whole blood using salt-saturation method. We used amplification refractory mutation system technique to find G1691A and G20210A variations. Results: We found two subjects with prothrombin G20210A mutation and three individuals with factor V Leiden variant, both in heterozygote state. The frequency of the polymorphisms were 1.79 and 2.68, respectively. No homozygote or compound heterozygote individual was detected for these two variants in this study. Conclusion: our findings about the polymorphisms frequency were different from what was detected in other provinces of Iran or in some region of neighboring countries. This discrepancy of the variant frequency can be explained by gene flow phenomenon.